Implantación de un sistema contable en la cooperativa de transporte mixto ciudad de Yantzaza Del Canton Yantzaza, provincia de Zamora Chinchipe, periodo octubre-diciembre del 2014 - Carrión Castillo, Verónica Elizabeth (2015)
Implementation of Accounting System in Cooperative Joint Transport Yantzaza City, Canton Yantzaza province of Zamora Chinchipe, it made pursuant to one of the pre-qualification as Engineering in Accounting and Auditing requirements. Public Accountant - Auditor CPA, the National University of Loja; as well as the main idea is to improve the administrative, accounting and control processes for cooperative members to achieve the objectives in the most effective and efficient manner. The purpose of this work is to implement the accounting system in the bus cooperative in order to provide information on their actual economic activities through the main accounting records for the different economic movements required for the provision of transport, thereby facilitating accurately determining the accounting and financial information that will serve as a basis for decisions of its managers and partners in a given period. The accounting process begins with the chart of accounts, user accounts, and the respective initial inventory records of transactions, majorization, trial balance, worksheet, getting to obtain the financial statements, which allowed them to determine the profitability Cooperative. Thus it can be concluded that the accounting process is favorable to Transport Cooperative, because he provided a tool to know the real economic situation and make sound decisions on time; therefore it is recommended to continue with this accounting system because it is the right to know the true cost of their operations.